Citizenship, neighborhoods and voting in Cartagena 1810-1834 - Monsalvo Mendoza, Edwin (Universidad Pedagógica y Tecnológica de Colombia, 2013)
The objective of this study is to describe the debates generated in Cartagena around the topic of the construction of citizenship. Our hypothesis is that the problem of citizenship was reduced to the discourses of inclusion/exclusion of certainsocial sectors in the elections. In turn, although this debate referred to some theoretical foundations based on the freedom to vote, and the consequent independence of the voter, in the end it was still heavily marked by the social characteristics of Cartagena society in the irst half of the XIX c. In this way, the ideals of theory clashed against the reality lived by elite and educated groups, which served as catalysts for the different liberal trends, this ended up imposing practicalconsiderations on the right to vote.